Izhodišča za izboljšanje korporacijskopravnega okolja delovanja inovativnih zagonskih podjetij - Podgorelec, Peter (Podjetje in delo, 2025)
A key objective of the next amendment to the Companies Act - ZGD-1N will be to create a more conducive national corporate-legal environment for investment in high value-added companies or companies with the potential to become such (start-ups). These baselines set out a range of possible legislative solutions based on a comparative legal analysis and, by publishing them, the wider professional community is invited to comment on them and, where appropriate, to propose further solutions. In any case, Slovenia should modernise its limited liability company law, especially in the direction of greater flexibility in financing methods and de-formalisation of certain procedures and transactions. The possible need for a simplified public limited company would need to be particularly well justified.
Keywords: corporate law; družba z omejeno odgovornostjo; korporacijsko pravo; limited liability company; poenostavljena delniška družba; simplified public limited company; start-upi; start-ups